Cholesterol ester storage disease with a novel LIPA mutation (L264P) that presented massive hepatomegaly: A case report. Issue 5 (18th September 2015) - Kuranobu, Naomi; Murakami, Jun; Okamoto, Ken; Nishimura, Rei; Murayama, Kei; Takamura, Ayumi; Umeda, Toshiko; Eto, Yoshikatsu; Kanzaki, Susumu
Abstract : Cholesterol ester storage disease (CESD) is an autosomal recessive disorder caused by deficient lysosomal acid lipase (LAL) activity, resulting in cholesteryl ester (CE) accumulation. CESD patients have liver disease associated with mixed dyslipidemia leading to liver failure. We here report the case of an 11‐year‐old male CESD patient with a novel mutation who had the chief complaint of massive hepatomegaly. The patient's liver reached to his pelvis, and his spleen was 2 cm below the costal margin. The patient had elevated serum liver enzymes and mixed dyslipidemia. The liver biopsy tissue showed characteristic CESD pathology, which included microvesicular steatosis, mild fibrosis and foamy macrophages. Electron microscopy showed a remnant cleft of CE crystals, and dried blood spot testing showed reduced LAL activity. We identified compound heterozygous mutations in the LIPA gene in this patient, namely, c.607G>C and c.791T>C. The former mutation was previously reported only in a Japanese patient, whereas the latter mutation is novel. The findings of this study suggest that LIPA gene mutations in Japanese CESD patients are different from those in Western patients. Although CESD is rare, it is likely that many patients are unrecognized or misdiagnosed, and thus the possibility of CESD should be considered in patients with hepatosplenomegaly and dyslipidemia.